Shakespearean Tragedy and Gender - Garner, Shirley; Sprengnether, Madelon (Indiana University Press, 1996)
These essays mount a powerful critique of the tragic hero as representative of the errors and sufferings of humankind. From a variety of critical perspectives-including feminist new historicism, psychoanalysis, poststructuralism, and autobiographical criticism-authors examine Shakespeare's construction of tragic subjectivity, the location of women in the scene of tragic action, and the social discourses that combine to elevate the hero's status while marginalizing, silencing, or eliminating female authority and presence. While considering Shakespeare's earliest attempts at tragedy in Richard III and Titus Andronicus, this volume also covers the major tragic period, giving special attention to Othello.